Heirs of thought. These Costa Rican poets were born between 1985 and 2000. - Guzman-Sierra, Silvia Elena (2021)
This essay is an exchange with the feminist thinker and writer Clorinda Matto de Turner.  It relates the thinking and creative practice of Costa Rican female poets of the younger generation, those born between 1985 and the year 2000, in order to raise the daily challenges they face in their creative processes, the publication of their works and their recognition.